New perspectives on utilization of CO2 sequestration technologies in cement-based materials. (22nd February 2021) - Liu, Baoju; Qin, Jiali; Shi, Jinyan; Jiang, Junyi; Wu, Xiang; He, Zhihai
Highlights: CO 2 sequestration technologies in cement-based materials was summarized. Effects of CO 2 curing on performance of CBM were reviewed in detail. The carbonated recycled aggregate concrete had the enhanced performance compared with recycled aggregate concrete. Abstract: With the development of the construction industry, global CO 2 emissions are closely related to the utilization of cement-based materials (CBM). The calcium-silicate-based cement, as well as construction and demolition waste is calcium-rich, and both of them are considered as the main sources of mineral carbonation to transform CO 2 into thermochemically stable carbonates. Therefore, accelerated carbonation can be used in not only the early-age curing stage but also the reused stage of CBM, providing an approach for large-scale CO 2 sequestration. This paper focuses on the carbonation mechanism, CO 2 curing technology, as well as the effects of accelerated carbonation on the microstructure, mechanical properties and durability of CBM in detail. The results showed that early-age CO 2 curing could densify the microstructure, thus enhancing the mechanical properties, impermeability and durability of CBM. In addition, CO 2 sequestration could improve not only the physical properties of recycled aggregates (RA) and waste cement, but also the microstructure and performance of prepared recycled concretes, thus promoting the reutilization of RA and waste cement in CBM. It follows that the correct utilization of CO 2 sequestration technologies in CBM can not only achieve environmental benefits, but provide a new perspective for the development of the construction industry. Finally, based on this review, limitations of the existing studies are identified and the prospects that might be helpful for potential further investigation are given on the utilization of CO 2 sequestration technologies in CBM.